2021
DOI: 10.3390/brainsci11091177
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Care Unit-Acquired Weakness and Positioning-Related Peripheral Nerve Injuries in COVID-19: A Case Series of Three Patients and the Latest Literature Review

Abstract: A subgroup of COVID-19 patients requires intensive respiratory care. The prolonged immobilization and aggressive treatments predispose these patients to develop intensive care unit-acquired weakness (ICUAW). Furthermore, this condition could increase the chance of positioning-related peripheral nerve injuries. On the basis of the latest literature review, we describe a case series of three patients with COVID-19 who developed ICUAW complicated by positioning-related peripheral nerve injuries Every patient pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…The frequency of non-vascular neurologic manifestations as encephalopathic, epileptic or neuromuscular disorders shows a large variability in the preexisting literature, depending on timepoint of assessment, qualification of the investigator, definitions of disorders and control for confounders. According to our data and in line with previous reports, no specific direct pathomechanism between those manifestations and COVID-19 became obvious [ 19 , 38 ]. The number of patients with positive PCR detection of the virus in CSF or brain tissue was negligible which supports previous results arguing against SARS-CoV-2-associated meningoencephalitis [ 7 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The frequency of non-vascular neurologic manifestations as encephalopathic, epileptic or neuromuscular disorders shows a large variability in the preexisting literature, depending on timepoint of assessment, qualification of the investigator, definitions of disorders and control for confounders. According to our data and in line with previous reports, no specific direct pathomechanism between those manifestations and COVID-19 became obvious [ 19 , 38 ]. The number of patients with positive PCR detection of the virus in CSF or brain tissue was negligible which supports previous results arguing against SARS-CoV-2-associated meningoencephalitis [ 7 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 91%
“…Several pathophysiological mechanisms have been proposed to explain neurological manifestations in COVID-19 [ 5 , 13 15 ]. However, as ICU patients not suffering from COVID-19 also frequently exhibit neurologic complications like encephalopathy, critical illness polyneuropathy/myopathy (CIP/CIM) or cerebrovascular disorders, the evaluation of a direct pathophysiological link between the virus and neurologic complications is challenging [ 16 19 ]. Furthermore, studies on neurologic manifestations of COVID-19 in- and outside the ICU are largely hampered by their retrospective design and its inherent biases, discrepancies in methodology, differences in definitions of neurologic disorders, sample size and reporting bias.…”
Section: Introductionmentioning
confidence: 99%
“…Although a significant improvement in prevalence rates of neurological diseases could not be shown, individual patients recovered, especially those with CIP/CIM, underlining the importance of neuro‐rehabilitation in severe COVID‐19 patients. Similarly, positioning‐related peripheral nerve injury was alleviated in one patient [ 39 ]. There are insufficient data of other infectious diseases to be compared to long‐term neurological deficits as described in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 54 studies, 11 studies reported on ischemic strokes and 41 studies reported on ICHs. There were two case reports on mononeuritis multiplex (10,11), one case report on brachial plexopathy (12), three case reports on critical illness myopathy or neuropathy (12)(13)(14), five studies on cerebral microbleeds (12,(15)(16)(17)(18), and one case report of posterior reversible encephalopathy syndrome (18). Lastly, there were two studies that reported venous causes for neurovascular complications (19,20) and two studies that used electroencephalogram to investigate the electrophysiologic changes of patients with COVID-19 on ECMO (21,22).…”
Section: Resultsmentioning
confidence: 99%